Politicians' Motivation, Role of Elections, and Policy Choices - Phongthorn Wrasai (Tinbergen Institute, 2005)
We develop a simple two period model to study the importance of motivational differences among politicians in describing the role of elections and explaining policy choices. In our model, politicians differ in their motives of running public office. Good politicians care about policies while bad politicians care about rent extraction. Voters want to control politician misbehavior and to select good politicians. We show that reelection concerns may compel a good politician not to implement a socially desirable policy if he sufficiently cares about the future. Second, reelection concerns may induce a bad politician not to undertake a socially undesirable policy. The reason for this is fear of being ruled by another bad politician if unseated. This finding exhibits the disciplining function of elections. A striking result in our paper is that bad politicians may act more in tune with the public interest relative to the good politicians.
Keywords: D72; D78; D82; 330; Politicians' Motivation; Role of Elections; Policy Choices; Politiker; Wahl; Neue politische Ökonomie; Ökonomische Theorie der Demokratie; Theorie; Politische Entscheidung